Novos desafios da tributação do software no Brasil sob as perspectivas do ICMS e do ISS: do corpus mechanicum ao cloud computing - Barthem Neto, Hélio (2016)
Abstract: The goal of the present study consists of examining the taxation of software focusing on the municipal service tax (ISS) and the tax on the circulation of goods and on services of interstate and Intermunicipal transportation and communication (ICMS). It is not properly a new theme and it was for sure deeply discussed along the last three decades. Nevertheless, the taxation of software is a topic of constant evolution, due to the fact that the software itself is a good that composes the information technology segment, which suffers changes in every minute, bringing more modernity to our day-by-day. The technological innovation introduces effective changes in the computing elements from the past and, as a consequence, the criteria used by the courts to define the tax treatment of software are also modified. Therefore, new challenges about the topic are set, especially in how to adapt the fundamentals before defined by the jurisprudence to guide the taxation of this important economic segment. Thus, reviewing relevant topics discussed in the past, such as the definition of the levy of these taxes based on technical and commercial concepts of computing program (standard software and personalized software), becomes extremely important. This study intends to demonstrate that, in spite of the fast and endless technological evolution, the taxation of software by ISS and ICMS must consider in the first place the characteristics of the legal transaction that supports the supply of the computer program, using its technical aspects as auxiliary elements to define the more adequate tax treatment.